Does al-Sha'rawi's Exegesis Portray Khayr in the Qur'an as Moral Virtue or as a Dynamic Theology of Divine-Human Reciprocity? - Falah, Muhammad Zulfikar Nur; Lathif, Rafiandra; Hanafi, Barda Royyan (QiST: Journal of Quran and Tafseer Studies, 2026)
Studies on the Qur'anic concept of khayr often emphasize its ethical dimension, yet they rarely explore its full semantic range and theological integration within modern exegesis. This gap becomes evident when considering al-Sha'rāwī's interpretations, which offer a rich but understudied perspective on Qur'anic vocabulary. Addressing this gap, the present study investigates the meaning of khayr in the Qur'an from al-Sha'rāwī's viewpoint by analyzing its linguistic forms, semantic layers, and contextual applications. The objective of this research is to classify and interpret khayr across its grammatical variations—such as ism, ism tafḍīl, and ṣifah mushabbahah—and to examine how these forms contribute to al-Sha'rāwī's integrative understanding of goodness. Using a qualitative literature review, the study applies the tafsīr mawḍū'ī method to collect and analyze Qur'anic verses containing khayr, focusing specifically on Q. 16:30, Q. 21:73 and 90, Q. 44:37, Q. 98:7, and Q. 100:8. These verses are categorized according to their i'rāb structures and semantic characteristics, supported by etymological and terminological analysis. The findings reveal that al-Sha'rāwī interprets khayr not merely as moral virtue, but as a dynamic theological and ethical concept encompassing 'ibādah, 'aqīdah, and akhlāq. He frames khayr as a unifying principle linking divine reward with human action, suggesting that true goodness integrates worldly benefit with spiritual consequence. The implications of this study underscore the importance of linguistic-thematic approaches in uncovering the depth of Qur'anic semantics. Its global contribution lies in offering a model for semantic-based Qur'anic interpretation that enriches discussions in moral theology, comparative scripture studies, and cross-cultural ethical discourse.